Intra- and inter-observer reliability of measurements on 3D images of the calcaneus bone. Issue 5 (6th July 2021) - Misselyn, Dominique; Caeyman, Aaron; Hoekstra, Harm; Nijs, Stefaan; Matricali, Giovanni
Abstract: Background: The use of the 3D orientation angle of the calcaneal posterior subtalar (PTC) joint facet might be superior to the Böhler's angle to evaluate the quality of reduction after performing an open reduction and internal fixation (ORIF) of displaced intra-articular calcaneal fractures (DIACFs). Methods : Three-Dimensional segmentations of the preoperative, postoperative and uninjured calcaneus of 54 patients with a DIACF were assessed by 4 observers with different medical backgrounds. After the delineating of the PTC on the 3D images, a MeVisLab™ software calculated the 3D orientation angle of the PTC, which was determined as the average of the angles between the normal vectors of the PTC and the main axis of the calcaneus, calculated by principal component analysis. The intraclass correlation coefficient (ICC) was used to determine the intra- and inter-observer reliability. Results : The ICC of the intra-observer measurements varied from 0.699 to 0.890. For the preoperative measurements an inter-observer ICC of 0.828 was calculated. For the postoperative measurements the calculated inter-observer ICC amounted 0.692. The inter-observer ICC of the uninjured measurements amounted 0.776. Discussion : Observation of the PTC on 3D images of the calcaneus shows a good intra- and inter-observer reliability, which means it is safe to use the 3D OAC of the PTC in clinical practice.